Smart Bin for the Separation of Waste using IOT - Radhika, M (International Journal of Computer Sciences and Engineering, 2025)
Nowadays garbage collection is a major problem in all cities. Even though there are big garbage bin in each street, it overflows and bad odour makes that area very uncomfortable. The concept of IOT is used in various applications. Here this paper uses IOT for the separation of waste by keeping different types of smart bins for plastics, glass or iron and organic wastes in each street. So that at the time of disposing the waste the bin senses the waste material through the sensor. There is a motor and sensors on the top of it that identify the type of waste. Here one moisturizer sensor is used for segregating the dry and wet waste. Once selection is decided the robotic arms push the wastes to the respective box in various methods. Through this the disposal of garbage can be made efficiently according to the various types of waste materials